GIS in assessing of landslide susceptibility and structural systems (2016)
Currently, geographic information systems (GIS) are a fundamental tool in the capture, processing, analysis and dissemination of spatial data. Geotechnical and structural engineering, where the characterization of materials and structures is important, GIS facilitate the inclusion of descriptive data called attributes to spatial or geographic records. In this paper two applications of this type of mapping is processing; The first has to do with the evaluation of susceptibility to landslide phenomena where two methodologies that divide the study area into cells of defined size are applied, GIS processing information from data capture to the generation of outputs graphs. The second application is geared towards identifying and analyzing the different structural systems, where the assessment of structural aspects contained performed in the Standard Seismic Resistant 2010 (NSR-10), the data are collected and included in the GIS systematically, in order that they are part of the attributes of each building represented by a polygon. The two applications are developed in the city of Tunja, Boyacá and intended to be part of a preliminary study of seismic vulnerability to substantiate a study of micro-zoning, necessary for the city. Such applications were not developed in the city and generate useful cartographic database data in decision-making for the planning and distribution of resources on issues related to seismic hazard and attention in areas of greatest vulnerability. How GIS appreciated facilitate processing of spatial and descriptive information and its importance in the analysis of spatial trends and characterization of geographic areas and buildings.